Case report: Mirror paraclinoid aneurysm associated with mirror clinoidal meningioma - Paitán, Alexander Feliciano Vilcahuamán; Gibbon, Frederico de Lima; Korotkov, Dmitriy; Castillo, Ileane Camallery; Moguel, Ambar E. Riley; Salvagni, Felipe Pereira; Chaddad-Neto, Feres (Frontiers in Neurology, 2024)
Introduction Clinoidal meningiomas and paraclinoid aneurysms are individually uncommon, with the coexistence of mirror paraclinoid aneurysms and clinoidal meningiomas presenting an even rarer scenario. While the association between meningiomas and aneurysms is documented, the simultaneous presence of mirror lesions for both pathologies is not reported in the literature. Clinical presentation We report a 62-year-old female with a three-month history of moderate bifrontal headaches. Magnetic Resonance Angiography (MRA) revealed mirror paraclinoid aneurysms, prompting surgical intervention. During the procedure, mirror clinoidal meningiomas were incidentally discovered. The left aneurysm was addressed first due to higher rupture risk, followed by the right aneurysm 3 months later. Both meningiomas were confirmed as Transitional Meningiomas (Grade 1; OMS, 2021). The aneurysms were successfully clipped, and the patient had an excellent postoperative outcome. Conclusion This case represents a unique occurrence of mirror ophthalmic segment internal carotid artery aneurysms associated with mirror clinoidal meningiomas, a combination not previously reported. Despite the limitations of MRA in detecting small meningiomas, it remains a valuable non-invasive screening tool for neurovascular diseases. The case underscores the need for further research to elucidate the association between cerebral aneurysms and meningiomas.